2011
DOI: 10.3345/kjp.2011.54.6.246
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of small for gestational age micropremies depending on how young or how small they are

Abstract: PurposeThe outcomes of small for gestational age (SGA) infants especially in extremely low birth weight infants (ELBWIs) are controversial. This study evaluated the mortality and morbidity of ELBWIs, focusing on whether or not they were also SGA.MethodsThe medical records of 415 ELBWIs (birth weight <1,000 g), who were inborn and admitted to the Samsung Medical Center neonatal intensive care unit from January 2000 to December 2008, were reviewed retrospectively. Mortality and morbidities were compared by body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Although this effect was more pronounced in cohort studies, it was also found in some case-control studies (Figure 3). The difference in GA between the SGA and the control group was particularly marked in the 3 studies (16, 33, 49) that only used BW as inclusion criterion. When these three studies were pooled, meta-analysis showed a MD in GA of 2.23 weeks (95% CI 1.66–2.79).…”
Section: Resultsmentioning
confidence: 99%
“…Although this effect was more pronounced in cohort studies, it was also found in some case-control studies (Figure 3). The difference in GA between the SGA and the control group was particularly marked in the 3 studies (16, 33, 49) that only used BW as inclusion criterion. When these three studies were pooled, meta-analysis showed a MD in GA of 2.23 weeks (95% CI 1.66–2.79).…”
Section: Resultsmentioning
confidence: 99%
“…B etween 11 and 22% of prematurely born infants have evidence of intrauterine growth restriction (IUGR) (1,2), yet the influence of fetal growth restriction on respiratory morbidity remains controversial. Some studies have highlighted that small size at birth was associated with a reduction in the incidence of respiratory distress syndrome (RDS) (3,4), but other studies suggested no influence (5-9) or a significant increased risk (10,11).…”
mentioning
confidence: 99%
“…Este último se define cuando su peso y/o longitud se encuentran dos o más desviaciones estándar (DE) por debajo de la media establecida para su población de referencia, su sexo y su EG 3,4 . Los pacientes con PBEG están generalmente asociados con la restricción del crecimiento intrauterino (RCIU), causada por un suministro inadecuado de oxígeno y nutrientes, atribuibles en la mayoría de los casos a insuficiencia placentaria 5 .…”
Section: Introductionunclassified